PERBEDAAN PENDAPAT AHLI NAHWU TENTANG FA`IL DILALAH DAN PENEMPATANNYA DARI PERSPEKTIF ALQURAN DAN BAHASA ARAB - Abdul Halim (SHAHIH (Jurnal Ilmu Kewahyuan), 2018)
“The practice of Islamic teachings would be more argumentative if based on religious texts, such as the hadith of the Prophet. The use of veils among Muslim women is allegedly based on a hadith about the veil of al-Bukhārī. This paper discusses the quality of the mat hadith, without neglecting the results of criticism sanad. Based on research conducted, sanad hadith narrated al-Bukhārī is qualified valid. Although the history of al-Bukhārī is valid, both redactional and substantial, it does not indicate the existence of a veil for Muslim women.”